Sistema de ecuaciones lineales para estudiantes del segundo grado de educacin secundaria en el trabajo remoto 2020 - Trujillo Lujn, Juan Carlos (2020)
The present work entitled "system of linear equations for students of the second grade of secondary education in remote work 2020", in which the real contextualization of EI N 80288 town center of San Isidro-Otuzco, place where the learning session was applied, in which the students were able to develop the competence "solves problems of regularity, equivalence and change" and performance; "Expresses with various representations his understanding of the solution of a systemof linear equations and" selects and combines more convenient strategies to solve a system of linear equations" In the development of the session motivating and challenging activities were applied, promoting the achievement of mathematical competencies and abilities. The pedagogical processes such as motivation, the exploration of previous knowledge, problematization, management and accompaniment, evaluation and transfer in the didactic processes and focus of the area were taken into account. The active and constant participation of the students was promoted individually and in groups, in the same way it was possible for them to relate their new knowledge with the previous ones. The strategies used were according to the interests and needs they presented.